PAPSO algorithm for optimization of the coil arrangement - Borowska, Bożena (Видавництво Львівської політехніки, 2011)
The Particle swarm optimization (PSO) is an efficient optimization algorithm for solving complex global optimization problems. However, In order to provide this algorithm to be efficient, it Is often necessary fo matte several numerical computations of the optimized function. To reduce the costs of compulations, the new Phase Angle Particle Swarm Optimization (PAPSO) algorithm was implemented In the proposed algorithm we gave up the velocity vector of particle. Instead of that the phase angle vector was introduced. The proposed algorithm was examined on four benchmark test functions and was applied far determination of the optimal geometry of the cylindrical coil arrangement. The results were then compared with performances of the standard PSO and the 6-PSO atgonthms in all cases.
Keywords: optimization; electromagnetism; particle swarm optimization; magnetic field